Effects of Tidal Events on the Water Quality in the Merbok Estuary, Kedah, Malaysia (Journal of Environmental Science and Natural Resources, 2016)
This study was carried out to observe effects of tidal events on the water quality parameters at Merbok estuary, Kedah, Malaysia. Twenty four hours sampling were conducted at Station 1, 2 and 3 from 12th November (spring tide) to 3rd December (neap tide) 2011 on weekly interval. Results showed that water quality parameters varied with the following ranges: temperature (26.10 - 30.7°C), pH (6.29 - 7.22), dissolved oxygen (0.65 - 5.48 mgL-1), salinity (0.50 35PSU), nitrate (0.037 - 0.647mgL-1), nitrite (0.09 - 0.36 mgL-1), ammonia N (0.03 - 3.05 mgL-1), phosphate (0.03 - 0.10mgL-1). Kruskal Wallis H test showed that water quality parameters were significantly different among sampling stations (p